327 The Impact of Implementation of Recommendations from the IFHD 2017 Annual Report in an Irish Model 3 Hospital. (16th September 2019) - Hearne, Siofra; Smyth, Hannah; Monahan, Pheadra; McGowan, Hugh; Timmins, Shirley; Hillary, Paddy; Mahapatra, Anant; Walsh, Alan; Conlon, Ciaran; Dunill, Eithne; Campbell, Eleanor; Carolann, Danielle; et al.
Abstract: Background: Hip fractures in the older person are associated with high mortality rates (NICE, 2011). Up to 40% of patients never regain their pre-fracture mobility, 10-20% never return to live at home. The Irish Hip Fracture Database (IHFD) National Report 2017 recommends appointment of an orthogeriatric consultant in this hospital to achieve IHFD standards 4 to 6. Methods: We analysed a subset of HIPE data collected for the IHFD in patients over 60 years over a three month period from September – November 2017 and compare it to September – November 2018 after introduction of an orthogeriatric service. We looked at geriatrician review, bone health assessment, falls assessment, discharge destination, 30-day re-admission rate and mortality during admission. Results: There were 45 hip fracture patients in each group. In the 2017 group, mean age was 79, female 64%; compared to mean age of 80, female 62.2% in 2018. In 2018, after the appointment of an orthogeriatrician, 95.6% of patients were seen by a geriatrician compared to 4.4% in 2017. In 2018, 97.7% received bone health assessment compared to 26.8% in 2017. In 2018 95.3% received specialist falls assessment, compared to 2.4% in 2017. Mean length of stay was 18 days in 2018 versus 13 days in 2017. 2.2% of patients were discharged to convalescence in 2018, 26.7% in 2017. 57.8% of patients were discharged to off-site rehabilitation in 2018 compared to 40% in 2017. 2.2% patients died during admission in 2018, 8.9% in 2017. In 2018, 6.7% of patients were readmitted within 30 days, 8.8% in 2017. Conclusion: Provision of rapid Comprehensive Geriatric Assessment to all hip fracture patients, reduces falls and fracture risk. There is evidence of improvement in IHFD standards 4-6, mortality rate and 30-day readmission rate. Moreover, the orthogeriatric service has led to increased referral to rehabilitation services ensuring optimal functional recovery.